Outcome Assessment According to the Thickness and Direction of the Acellular Dermal Matrix after Implant-Based Breast Reconstruction - Joon Hur (Hindawi Limited, 2021)
Purpose. The acellular dermal matrix plays an important role in reinforcing thin mastectomy skin and repositioning the implant in prosthetic breast reconstruction. As the concept of prepectoral plane has become widespread, the role of the acellular dermal matrix has become increasingly important. However, evidences and standards for appropriate thickness and direction during placement remain insufficient. This study is aimed at testing the assumption that differences in the acellular dermal matrix thickness and orientation during placement may affect surgical outcomes including the incidence of postoperative complications. Methods. This was a retrospective single-centered analysis of 43 patients (50 breasts) who underwent implant-based reconstruction with MegaDerm® (L&C Bio, Seoul, Korea) and 23 patients (23 breasts) who underwent implant-based reconstruction with DermACELL® (LifeNet Health, Virginia Beach, VA, USA), two types of human-derived acellular dermal matrix. All surgeries were performed by a single surgeon. Demographic variables, surgery-related factors, and complications were compared between a thick matrix group (1.5–2.3 mm) and a thin matrix group (1.0–1.5 mm). The same processes were performed in the nonreverse and reverse matrix insertion groups. Results. Baseline demographics and surgery-related data were summarized according to matrix thickness and direction. There were no significant intergroup differences in the demographic variables such as history of smoking, radiation, or chemotherapy. The mean drain volume was significantly higher in the thick matrix group than that in the thin matrix group (p=0.0445). However, there were no significant differences in overall complication rates by matrix thickness (p=0.3139). Additionally, there were no significant differences in complications between the nonreverse and reverse matrix insertion groups (p=0.538). Conclusion. Our findings suggest that patients with a thick acellular dermal matrix need a prolonged period for engraftment. However, the thickness did not directly affect the surgical outcomes between the thick and thin matrix groups. Likewise, the orientation in which the acellular dermal matrix was inserted did not affect the surgical outcomes including postoperative complications.